Growth changes associated with feeding Clarias gariepinus with mouldy feeds (2007)
This study was undertaken to determine the effects of consumption of mouldy feeds on the growth of the African catfish CIarias gariepinus. Forty-five juvenile fishes were maintained on mouldy feed ration while another forty-five served as controls. The control fishes remained healthy and steadily gained weight, reaching about 68% of their starting weight on the last day of the feeding trial. The test fishes in all the groups showed a significant decrease in weight gain comparable to the control fishes by the 2-way analysis of variance (ANOVA) and Duncan's multiple range test at 95% confidence interval (p<0.05). The study showed that feeding mouldy rations to Clarias gariepinus would result in decrease weight gain. This could be associated with the fact that many fungi elaborate mycotoxins and potent anti nutritional factors. Wholesome, dry and freshly compounded rations is advocated for intensively managed fishes.